2021
DOI: 10.3390/ijms22052481
|View full text |Cite
|
Sign up to set email alerts
|

Differential Morpho-Physiological and Transcriptomic Responses to Heat Stress in Two Blueberry Species

Abstract: Blueberries (Vaccinium spp.) are highly vulnerable to changing climatic conditions, especially increasing temperatures. To gain insight into mechanisms underpinning the response to heat stress, two blueberry species were subjected to heat stress for 6 and 9 h at 45 °C, and leaf samples were used to study the morpho-physiological and transcriptomic changes. As compared with Vaccinium corymbosum, Vaccinium darrowii exhibited thermal stress adaptation features such as small leaf size, parallel leaf orientation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Next-generation sequencing has become a powerful platform to elucidate molecular mechanisms in many research fields due to its rapidity and cost-effectiveness ( Gao et al., 2018 ; Callwood et al., 2021 ; McEvoy et al., 2022 ). The comprehensive data generated facilitates the development of genetic analyses and functional genomics studies between plant species, specifically for non-model plants and tree species ( Kulkarni et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing has become a powerful platform to elucidate molecular mechanisms in many research fields due to its rapidity and cost-effectiveness ( Gao et al., 2018 ; Callwood et al., 2021 ; McEvoy et al., 2022 ). The comprehensive data generated facilitates the development of genetic analyses and functional genomics studies between plant species, specifically for non-model plants and tree species ( Kulkarni et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These wild species could be a repository of favorable alleles for future use in introgression programs. Recently, we have shown that the southern species V. darrowii exhibits a differential response of morpho-physiological and molecular mechanisms compared to the V. corymbosum plants under heat stress [ 25 ]. Thus, analyzing the genetic structure of species can help identify diverse lineages and play an important role in breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Plants handle abiotic stress through cellular level tolerance by maintaining metabolic homeostasis, cellular membrane stability, osmotic adjustments, management of oxidative stress, production of stress-responsive genes and proteins and secondary metabolites, and lipid reprogramming ( Li et al., 2015 ; Nisarga et al., 2017 ; Kiranmai et al., 2018 ; Callwood et al., 2021 ; Mulozi et al., 2023 ). By altering the expression of many genes through complex signaling pathways, plants have developed adaptive mechanisms for abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%